Incentives for Danish healthcare management based on a pilot outcome-based, patient-centric management model in psoriasis and psoriatic arthritis: the non-interventional IMPROVE study - Simon Francis Thomsen; Lone Skov; Lars Erik Kristensen; Morten Størling Hedegaard; Jakob Kjellberg; Tanja Schjødt Jørgensen; Søren Brenøe; Rikke Dodge (BMC, 2020)
Abstract Background Psoriasis (PsO) and psoriatic arthritis (PsA) are chronic diseases that affect patients' quality of life. The purpose of the present study was to develop a pilot outcome-based, patient-centric management model for PsO and PsA. Methods The non-interventional IMPROVE (Incentives for healthcare management based on patient-related outcomes and value) study being conducted in Denmark consists of 5 phases: 1) collecting real-world evidence to estimate treatment patterns and disease burden to the healthcare sector and patients; 2) identifying disease aspects which matter most to patients by use of concept mapping; 3) conducting interviews with healthcare professionals and patient organization involved in a typical PsO or PsA patient journey in order to determine relevant measures to quantify patient-identified outcomes; 4) developing a value-based remuneration model based on outcomes from phases 1-3; and 5) testing the outcome-based model in pre-selected hospitals in Denmark. Results Both PsO and PsA are associated with multiple co-morbidities, increased healthcare costs, and loss of earnings. Seven important 'clusters' of disease aspects were identified for both PsO and PsA, including uncertainty about disease progression and treatments, as well as inter-personal relations with healthcare providers. Hospital-based treatment was associated with high treatment costs. Although the outcome-based model could result in strategic behavior by doctors, those involved in defining the best outcome goals consider it unlikely. Conclusion The new patient-centric outcome-based management model is expected to support optimal treatment and secure best possible outcomes for patients suffering from PsO or PsA. The practical implication of the present study are that the models developed are expected to increase focus on patient-centered healthcare, and help eliminate some of the inappropriate incentives that exist in activity-based remuneration systems. Trial registration Not applicable; data collected from patient registries in Denmark.